LIQUIDITY RATIO ANALYSIS FOR FINANCIAL PERFORMANCE ASSESSMENT (CASE STUDY: UPK LANGGENG MAKMUR, PRINGAPUS DISTRICT, SEMARANG REGENCY) - Widowati, Lis; Kurniawati , Andi (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This research aims to analyze liquidity ratios with the aim of being used as an assessment tool to financial performance at UPK Langgeng Makmur. This research uses a descriptive qualitative approach method. The data studied is in the form of UPK Langgeng Makmur's financial reports from 2019 to 2021. The standard used is the liquidity ratio standard according to Kasmir. From the results of calculating the average liquidity ratio, the financial performance condition of UPK Langgeng Makmur is said to be good. From the calculation of the current ratio from 2019 to 2021, it can be said to be good, although everything is still below the standard current ratio, namely 200%, but it is still said to be good because it is not less than 150%. Meanwhile, according to quick ratio calculations in 2019 and 2020 it was declared "very good" because it was above the standard ratio, namely 150%, but in 2021 it decreased slightly and was below the standard ratio but not less than 100% so it could still be said to be "good". And according to the calculation of the cash ratio and inventory to net working capital in the three years, the financial performance was said to be "very good" because it was far above the standard ratiomeasure. The general conclusion of this research is that the financial performance in 2019 to 2021 at UPK Langgeng Makmur can be said to be good and not too bad because all ratio calculations show good percentages